A Preliminary Study on Motor Vehicle Crash Characteristics Involving Motorcycle and Passenger Vehicle in Malaysia - Kak, D.W.; Zainal Abidin, A.N.S. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Motorcycle is the primary mode of motor transportation in ASEAN countries including Malaysia. Nonetheless, motorcycle crashes have contributed more than 50% of the total number of fatalities due to motor vehicle crashes. High numbers of fatalities in motor vehicle crashes are a significant concern to Malaysia. On average, the number of fatalities increased by 4% every year. To address this problem, more intervention shall be taken to reduce motorcycle-related motor vehicle crashes. Passenger vehicle is the most frequent crash partner of motorcycle in Malaysia, thus, the characteristics of this kind of crashes shall be studied holistically to understand the contributing factors to crashes involving passenger vehicle and motorcycle. To achieve the objectives, this study has analysed 55 cases of crash involving motorcycle and passenger vehicle, which are obtained from in-depth crash investigation process from June 2016 until July 2017. The in-depth crash investigation has collected and analysed vehicle and site parameters including the crash configuration. It was found that the passenger vehicle was at fault in more than 60% of the investigated cases. The crashes mostly occurred whenever the passenger vehicle was changing lane to the left and was making a right turn in the junction. This indicated that the passenger vehicle drivers were unaware or overestimated the distance between the motorcycle and their vehicle. Therefore, new technology, which can detect the position and distance of motorcycles around the passenger vehicle, can possibly alert the driver from making inaccurate decisions while attempting to change lane or making a right turn.